The Effect of Service Quality and Price on Customer Satisfaction (Study at a heavy equipment company in the city of Bandung) - Galih Kharisma Bulan; Irena Larashati (STMIK Mardira Indonesia, Bandung, 2022)
Researchers researched to determine the effect of service quality and price on customer satisfaction at one of the heavy equipment companies in the city of Bandung. Moreover, this research analyses the factor that has the most dominant influence on service quality and price on customer satisfaction at one of the heavy equipment companies in Bandung. As many as 57 consumers became the object of this study using a questionnaire.Based on research using path analysis, it can see that the variables of service quality and price at one of the heavy equipment companies in the city of Bandung are declared valid. Therefore, the conclusions and considerations related to the research results are paying attention to service quality and price to increase customer satisfaction.The results of the study show that Service Quality (X1) has a significant influence on Customer Satisfaction (Y). then Price (X2) significantly influences Customer Satisfaction (Y). To improve service quality, companies should pay more attention to service quality dimensions because a slight deficiency can satisfy consumers and impact consumer satisfaction. For example, if there are bad complaints, it will reduce consumer confidence in the product. Therefore, if a complaint occurs, the company must restore customer trust by evaluating the quality of service properly so that customers feel satisfied, one of which is by giving customer surveys when customers are and after using products/services so that customer feelings can be maintained. In terms of price, companies should evaluate more when setting prices for a product/service, such as considering market conditions and the number of competitors. Then, the company can package excellent and attractive price offers such as discounts or bonuses to customers to increase customer satisfaction.Keywords : Service Quality, Price, Customer Satisfaction